Relationship between nausea and vomiting and physical activity in patients with lung cancer undergoing first chemotherapy - Bai, Liandi; Ni, Li; Lu, JianHong; Zhang, Yue Yu; Yin, Yuanyuan; Zhang, WeiYing; Duan, Xia (Frontiers in Oncology, 2024)
Objective Nausea and vomiting are the distressing and debilitating side effects of chemotherapy. This study explores the relationship between the degree of nausea and vomiting and physical activity in patients with lung cancer during the first chemotherapy cycle. Design A total of 107 patients with lung cancer who received platinum drugs during chemotherapy in a hospital in Shanghai, China, in 2023 were involved in this study. Data were collected with medical record system and self-reported questionnaires.Questionnaires included the International Physical Activity Questionnaire (IPAQ) and Index of Nausea, Vomiting, and Retching (INVR). IPAQ was used before chemotherapy; INVR was used on the second and sixth day of chemotherapy, followed by the analysis of the correlation between physical activity status and degree of nausea and vomiting during chemotherapy. The influencing factors of nausea and vomiting during chemotherapy in patients with lung cancer were analyzed using logistic regression analysis. Results More than half of the patients experienced nausea, vomiting or retching related symptoms after chemotherapy, and the proportion of moderate to high physical activity was 50.5%. Univariate analysis showed that the degree of nausea and vomiting was influenced by factors such as age, gender, and history of drinking (P < 0.05). The degree of nausea and vomiting was negatively correlated with physical activity (P < 0.05). The multivariate linear analysis showed that gender, history of drinking, and moderate and high physical activity are contributing factors to nausea and vomiting during chemotherapy (P < 0.05). Conclusion Moderate and high physical activity before chemotherapy is a protective factor for nausea and vomiting in patients with lung cancer. Physical activity can not only improve the degree of nausea and vomiting in patients with lung cancer but also reduce the incidence in these patients during the first chemotherapy cycle.